ANGKA KEBUNTINGAN KAMBING LOKAL PALU HASIL IB_PERTAMA MENGGUNAKAN SPERMA CAIR SUPLEMENTASI Leucocephala TANNIN - Mirajuddin, Mirajuddin (FAPETKAN UNTAD, 2011)
An experiment on the conception rates of local Palu goat artificially inseminated with sperms that were prepared in vitro with supplementation of tannin from Leucocephala with a glucose extender was done in Palu and Sigi District, Central Sulawesi from June to November 2009. The sperm donors were 2 Ettawa Crosses aged about 2.5 years from which the sperms were collected with artificial vagina. Normal ejaculates (based on microscopic as well as macroscopic analyses) were prepared into liquid sperms suitable for artificial insemination (AI). A diluted sperm with 18.9% glucose extender served as the control (K0) and this was directly (day 0 after dilution) used to inseminate 19 PGF2α-synchronized goats. For treatment group, a dlituted sperm was supplemented with Leucocephala tannin (2.5% per ml sperms) and was used to inseminate 22 female goats after being frozen for 14 d at 14°C. Spermatozoa concentration for the two preparations was similar (200 x 106 cell/ml/AI). It was found that the conception rate for the control group was 73.68% while for the treatment group was 95.45%.Key words : Artificial Insemination (AI), conception rate, Leucocephala Tannin, local goat Palu, sperm preparation.